2021
DOI: 10.31925/farmacia.2021.3.15
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Cytotoxicity Assessment of New 4-Benzyl-1,3-Oxazole Derivatives Incorporating 4-[(4-Bromophenyl)sulfonyl]phenyl Fragment

Abstract: Herein we present the design, synthesis, characterization, and cytotoxicity assessment of seven compounds derived from phenylalanine that incorporate a 4-[(4-bromophenyl)sulfonyl]phenyl fragment: four open-chain products (one N-acyl-α-amino acid, one N-acyl-α-amino acyl chloride, two N-acyl-α-amino ketones), and three five-membered heterocycles with two heteroatoms (O and N): one 2-aryl-4-benzyl-1,3-oxazol-5(4H)-one, and two 2-aryl-4-benzyl-1,3-oxazoles with p-tolyl, and m-xylyl substituent, respectively, in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Thus, the mass spectrum of imidazole shows a high abundance of the aziridinium cation at m/z 40. In the literature, deuterium labelling experiments have shown that the loss of hydrogen atoms is specific to positions 4 and 5, while the loss of HCN is less specific, starting in the order of 2 > 4(5) > 1 [32][33][34][35][36][37].…”
Section: Physicochemical Characterization Of the Intermediated Productsmentioning
confidence: 99%
“…Thus, the mass spectrum of imidazole shows a high abundance of the aziridinium cation at m/z 40. In the literature, deuterium labelling experiments have shown that the loss of hydrogen atoms is specific to positions 4 and 5, while the loss of HCN is less specific, starting in the order of 2 > 4(5) > 1 [32][33][34][35][36][37].…”
Section: Physicochemical Characterization Of the Intermediated Productsmentioning
confidence: 99%